Psychology Doctoral Program Experiences and Student Well-Being, Mental Health, and Optimism During the COVID-19 Pandemic - Syropoulos, Stylianos; Wu, Deborah J.; Burrows, Brooke; Mercado, Evelyn (Frontiers in Psychology, 2021)
In a sample of 916 doctoral students from 144 universities across the United States, we examined psychology graduate students’ experiences in their programs, as well as their mental health, well-being, and optimism during the onset of the COVID-19 pandemic. In a path model, we found that students’ psychological experiences in their programs (i.e., social belonging, threat, and challenge) were associated with better mental health and well-being, which in turn was associated with greater optimism about the future during the COVID-19 pandemic. These findings were also corroborated in students’ open-ended responses regarding how COVID-19 has impacted their lives. Findings varied by racial, gender, and sexual identities, as racial minorities, LGBTQ+ students, and women expressed more negative psychological experiences in their programs. We outline suggestions for graduate programs to support their graduate students, which include facilitating social connection, providing encouragement, and emphasizing students’ well-being over their productivity as the current pandemic persists.